Investigation on microstructures and mechanical properties of AlCrN coatings deposited on the surface of plasma nitrocarburized cool-work tool steels. (November 2015) - Chen, Wanglin; Zheng, Jie; Meng, Xianna; Kwon, Sikchol; Zhang, Shihong
Abstract: AlCrN coating which has been widely applied in industrial application was produced on the surface of nitrocarburized SKD 11 cool-work tool steel by physical vapor deposition (PVD) method. The effects of nitrocarburizing pretreatment and PVD deposition temperature on microstructures, mechanical and tribological properties of the coatings were investigated. The results show that the AlCrN coating consists of an inner CrN adhesion layer with columnar growth and an outmost AlCrN work layer with planar growth, and the AlCrN coating shows a superior hardness of about 43 GPa. The nitrocarburizing pretreatment considerably improve adhesion strength, load capacity and wear resistance of duplex coated samples when compared with the single AlCrN coated samples. The improved mechanical and tribological properties are mainly related to the thicker nitrocarburizing layer and the gradient in the hardness profile of the duplex coating. In addition, the nitrocarburizing-PVD AlCrN duplex coated samples can be further enhanced by increasing deposition temperature of PVD coatings. The main wear mechanisms of duplex coated samples are oxidation wear or oxidation wear and adhesion wear, whereas the main wear mechanisms of single AlCrN coated samples are spalling and chipping wear as well as oxidation wear. Highlights: AlCrN nanomultilayer with a superior hardness of 43 GPa consists of alternatively (Cr, Al)N sublayers. Nitrocarburizing (PN) improves mechanical and tribological properties of duplex coatings. Duplex coated samples are further enhanced with the deposition temperature. Wear mechanisms of the coatings with and without NP were investigated.